Multi-stage composite micro-nano particle with wide spectrum regulation and control performance and preparation and application of multi-stage composite micro-nano particle
By designing multi-stage composite micro-nano particles with wide spectrum regulation performance, combining the structure of the core, intermediate layer and outer layer, the problems of limited reflection band and poor stability in the prior art are solved, and efficient radiation refrigeration performance and material stability are achieved. , suitable for fiber material applications.
Patent Information
- Application Number
- CN202411749312.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2044-12-02
AI Technical Summary
In the prior art, the reflection band of a single nanoparticle coating is limited, and the effect of rare earth phosphate composite salts and polymer materials is weak, resulting in the fiber performance being affected; the porous structure size is uncontrollable and cannot be added to the base, resulting in the particles being easily shedded and Poor stability; the coating is easy to fall off, and effective radiation refrigeration performance cannot be achieved.
Multi-stage composite micro-nano particles with wide spectrum regulation performance, including core particles, intermediate particles and outer organic matter, are adopted to control the particle size and distribution of core particles to achieve high reflection of sunlight in the range of 0.2~2.5μm. And efficiently emit heat radiation within the atmospheric window through the intermediate layer nanoparticles, combining the functional functional groups of the outer layer silane coupling agent to enhance interface stability and dispersion.
It achieves high reflectivity in the range of 0.2~2.5μm and high emissivity in the range of 2.5~15μm, improves the radiation refrigeration performance of the fiber, enhances the dispersion and stability of the material, and is suitable for outdoor clothing and building materials.
Smart Images

Figure CN119221144A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of radiation cooling micro-nano particles, and relates to a multi-level composite micro-nano particle with wide spectrum control performance, and a preparation method and application thereof. Background Art
[0002] Radiative cooling is a performance that achieves a cooling effect by blocking sunlight and emitting infrared radiation to transfer the heat of an object to outer space.
[0003] Chinese patent CN115365097B discloses the use of inorganic nanoparticles such as silicon dioxide, zinc oxide, titanium dioxide and aluminum oxide as finishing agents coated on the fiber surface as a passive radiation cooling coating; Chinese patent CN112851945B discloses the use of organic silicon microspheres with daytime passive radiation cooling effect dip-coated on fabrics; Chinese patent CN115897242A discloses the use of inorganic micro-nano particles such as SiO2, SiC, Al2O3, TiO2, BaSO4 and CaCO3 added to fiber-forming polymers, and applied to yarns through a sizing coating process to obtain microporous radiation cooling yarns; Chinese patent CN115434151A discloses the use of polymers The dispersion of dimethylsiloxane and inorganic nanoparticles and the modified organic pigment solution are sprayed on the fabric in sequence to obtain a colored passive radiation coating fabric, wherein polydimethylsiloxane is used as a binder between the inorganic nanoparticles and the fabric, the inorganic nanoparticles are silica, titanium dioxide, aluminum oxide, aluminum phosphate, barium sulfate, etc., and the modified organic pigment is a composite particle of polymer-wrapped organic pigments; Chinese patent CN117304717A discloses a method for preparing a silica composite refrigeration coating and refrigeration film, the structure of the silica composite material contains silica microspheres and silica nanoclusters on the surface of the microspheres, and the high roughness of the silica particle clusters can provide a self-cleaning function. However, the above patents all use a single nanoparticle coating with a limited reflection band.
[0004] Chinese patent CN117468119A discloses adding rare earth phosphate complex salt to polymer material to produce passive cooling functional fiber through melt spinning process. However, the interaction between rare earth phosphate complex salt and polymer substrate is weak, which affects the fiber performance.
[0005] Chinese patent CN117164939A discloses a micro-nano porous-granular composite radiation cooling thin film coating and its preparation method, the thin film coating has a micro-nano pore structure and a nanoparticle structure; Chinese patent CN115323801A discloses adding inorganic particles such as alumina, silicon dioxide, silicon carbide, silicon nitride, aluminum phosphate, barium sulfate and titanium dioxide to a porous material, and then coating it on the surface of a substrate to obtain a coated textile with a passive radiation cooling function, wherein the inorganic particles and the porous structure are independently distributed on the surface and inside of the radiation cooling layer. However, the size of the porous structure in these two patents is uncontrollable, and it cannot be added to the inside of the substrate. It can only be coated on the surface of the substrate as a coating material, resulting in easy detachment of particles and poor stability.
[0006] Chinese patent CN112961533B discloses a radiation cooling coating formed by periodically arranging core-shell composite microspheres composed of inorganic powder with a solar spectrum reflectivity higher than 0.85 as the core and a high molecular polymer with a mid-infrared band emissivity higher than 0.85 as the shell; Chinese patent CN116285183A discloses a precursor of a radiation cooling coating or film material with thermal conductivity prepared by mixing prepared boron nitride hollow microspheres with an organic polymer; Chinese patent CN117447862A discloses a Geopolymer coatings of inorganic particles, including alkali-activated metakaolin, BaSO4 and silica nanospheres, provide sunlight reflection and infrared emission performance; Chinese patent CN117364025A discloses a method for preparing a band-selective infrared regulation and radiation cooling coating, based on dielectric constant near-zero ceramic Al-doped ZnO nanoparticles, which has a simple structure and can be prepared on a large scale at low cost, using the bottom Al metal layer to provide reflection, and Al-doped ZnO nanoparticles, whose dielectric constant near-zero and plasmon properties provide 5~8 μm broadband radiation performance. However, the coating of the above patent is easy to fall off and cannot be added to the substrate to bring about radiation cooling performance.
[0007] Chinese patent CN117382272A discloses a double-layer structure film with an organic radiation layer and a nanoparticle-containing heat-resistant layer, wherein the radiation layer material is an organic material with an absorptivity greater than 80% in the mid-infrared band, and the heat-resistant layer material includes an organic base material and inorganic nanoparticles dispersed in the organic base material, wherein the inorganic nanoparticles have an absorptivity greater than 80% in the near-infrared band; Chinese patent CN115610060A discloses a radiation cooling film with micropores and inorganic particles distributed inside, wherein the inorganic particles and the internal micropores cooperate to reflect sunlight irradiated on the radiation cooling film. However, these patents are membrane structures and cannot be combined into other substrates as additives. The membrane material has poor air permeability and is limited in usage scenarios, and cannot be combined with fibers for use in fabrics.
[0008] Chinese patent CN117364327A discloses the use of micro-nano fiber spinning technology to prepare micro-nano fiber yarns, and then weaving the micro-nano fiber yarns into a double-layer micro-nano fiber fabric with a daytime cooling function, wherein the upper layer is a fabric woven from mid-infrared emitting, hydrophilic, and thermally conductive yarns, and the lower layer is a fabric woven from mid-infrared emitting, hydrophobic, and thermally conductive yarns; Chinese patent CN114232108B discloses a method for preparing a three-dimensional porous micro-nano composite material and its daytime radiation cooling effect, wherein silicon dioxide and titanium dioxide nanophotons are embedded between micro-nano fibers of a beaded structure in nanofibers constructed by electrospinning technology, because the inherent porous structure and micro-nano fiber size enable the three-dimensional porous micro-nano material constructed by it to have a Mie scattering effect within the solar spectrum band (0.2~2.5 μm) and reflect sunlight, and the inherent mid-infrared absorption characteristics of nanophotons and fiber materials themselves enable the material to have mid-infrared emission capabilities within the mid-infrared spectrum band. These two patents combine functional materials into fiber bundles through nano-spinning, and change the distribution of pores inside the fabric through the design of the fabric structure. Based on Mie scattering, the fabric is given the ability to reflect sunlight within the solar spectrum band. Based on the light absorption characteristics of silica, titanium dioxide and fiber materials, the fabric is given the ability to emit mid-infrared radiation to achieve radiative cooling. However, in this type of solution, the fabric is designed as a multi-layer structure of micro-nano fibers, the strength of the fabric is reduced, the radiative cooling ability is weak, the radiation range cannot be finely controlled, and the mid-infrared emission ability is insufficient.
[0009] Therefore, it is of great significance to study a multi-level composite micro-nano particle with wide spectrum regulation performance and its preparation and application to solve the problems existing in the prior art. Summary of the invention
[0010] The purpose of the present invention is to solve the problems existing in the prior art and provide a multi-level composite micro-nano particle with wide spectrum control performance and its preparation and application.
[0011] To achieve the above object, the technical solution adopted by the present invention is as follows:
[0012] Multi-level composite micro-nano particles with wide spectrum control performance, including core particles, middle layer particles and outer layer organic matter, wherein the middle layer particles are uniformly grown on the surface of the core particles and are coated by the outer layer organic matter;
[0013] The inner core particles are inorganic particles A with a particle size range of 50-500 nm, the middle layer particles are inorganic particles B with a particle size range of 1-20 nm, and the outer layer organic matter is a silane coupling agent;
[0014] The inorganic particles A are titanium dioxide, silicon dioxide or zinc oxide, and the inorganic particles B are one or more of vanadium oxide, tungsten oxide, aluminum oxide, magnesium oxide, zirconium oxide and iron oxide;
[0015] The size of the core particles affects the reflectivity of sunlight, so the core particles with a particle size range of 50-500 nm are selected in the present invention. In addition, the particle size will also affect the uniformity of its dispersion in the matrix, so the particle size should not be too large; and the size range of the intermediate layer nanoparticles is within 1-20 nm, which can ensure its uniform loading on the surface of the core particles and form a relatively continuous covering layer;
[0016] The synergistic effect of the inner core particles and the middle layer particles enhances the radiative cooling effect, including: (1) the inner layer dominates the reflection of short-wavelength light (reducing the temperature rise of the material), and the outer layer dominates the long-wavelength thermal radiation (enhancing the heat dissipation of the material). The effective combination of the two improves the cooling efficiency; (2) The size distribution control and interface property optimization of the nanoparticles can promote thermal energy transfer and spectral selectivity; (3) The inner layer particles and the outer layer particles may form a heterojunction. The heterojunction interface promotes the localization of electromagnetic waves, thereby enhancing the radiation performance in the mid- and far-infrared regions. At the same time, the formation of the heterojunction can promote heat conduction and heat dissipation at the interface. The optimized thermal channel helps to transfer heat from the inner core to the outer layer more quickly and radiate it efficiently; (4) The heterojunction material can optimize the synergistic effect of reflection and emission under multiple spectra, and effectively regulate the photothermal effects of different spectral bands.
[0017] The terminal functional groups of one part of the silane coupling agents are hydrophilic functional groups, while the terminal functional groups of the other part of the silane coupling agents are hydrophobic functional groups; the silane coupling agents with hydrophobic terminal functional groups are distributed between different intermediate layer particles, providing additional chemical stability and dispersion stability, thereby achieving a multifunctional synergistic effect.
[0018] As the preferred technical solution:
[0019] As described above, the multi-level composite micro-nano particles with wide spectrum regulation performance, the silane coupling agent with a hydrophilic terminal functional group is one or more of 3-aminopropyltriethoxysilane (APTES), aminopropyltrimethoxysilane (APTMS), γ-methacryloxypropyltrimethoxysilane (MPS), 3-carboxyethyltriethoxysilane (CTES), 3-mercaptopropyltrimethoxysilane (MPTMS), 3-trihydroxypropyltrimethoxysilane (THPTMS), dihydroxydimethoxysilane (DHDMS) and γ-ethoxytrihydroxymethylsilane (ETHOMS), and the terminal functional group is hydrophobic. The water-functional silane coupling agent is vinyl triethoxysilane (VTES); APTES can introduce amino groups (-NH2) to enhance the binding with the core particles; APTMS can introduce methoxy groups (-OCH3) for further crosslinking and stabilization; MPTMS can introduce thiol groups (-SH) to increase the binding ability and stability to metal ions; MPS can introduce methacrylate groups (-CH2=C(CH3)COO-), CTES can introduce carboxyl groups (-COO-), VTES can introduce olefinic groups, and THPTMS, DHDMS and ETHOMS can introduce hydroxyl groups (-OH).
[0020] Selection of silane coupling agents: Adding a variety of silane coupling agents to simultaneously graft hydrophobic functional groups (such as alkenyl) and hydrophilic functional groups (such as hydroxyl, carboxyl, amino, and thiol) on the surface of the core particles; the synergistic effect of multiple functional groups can bring more functionality and better control the selectivity of the reaction in subsequent steps. The details are as follows:
[0021] 1) Synergistic effect of multiple functional groups: Grafting hydrophobic and hydrophilic functional groups simultaneously can achieve multifunctionality on the particle surface. Hydrophilic functional groups (such as hydroxyl, carboxyl, amino, and thiol) can provide good water-phase dispersibility and chemical reactivity, which is conducive to the subsequent growth of metal oxide nanoparticles; while hydrophobic functional groups (such as olefinic groups) can not only provide excellent organic solvent dispersibility and certain specific chemical stability, but also self-aggregation in hydrophilic media can avoid the coverage growth of metal ions, thereby ensuring that part of the silane coupling agent can still be retained on the surface of the core particles after the growth of the intermediate layer. In addition, the synergistic effect of hydrophobic and hydrophilic functional groups can reduce the agglomeration between particles, thereby ensuring that the particles remain well dispersed in the solvent or during the reaction process, further ensuring the uniform growth of nanoparticles.
[0022] 2) Selective coordination reaction of silane coupling agents. Silane coupling agents containing specific functional groups (such as amino, hydroxyl, etc.) are selected. These groups can form weak interactions with metal precursors without causing strong coordination. The active sites generated by the pretreatment of the surface of the core particles serve as growth sites, making the metal precursor more inclined to grow on the surface of the core particles driven by thermodynamic stability.
[0023] 3) Good interface compatibility: The simultaneous grafting of hydrophilic and hydrophobic functional groups can achieve good dispersibility and interface compatibility of particles in different matrices, meeting the application requirements in different matrices.
[0024] As described above, the multi-level composite micro-nano particles with wide spectrum regulation performance have a particle size range of 100nm~3μm.
[0025] As described above, the multi-level composite micro-nano particles with wide spectrum regulation performance have a mass ratio of inner core particles, middle layer particles and outer layer organic matter of 60~80:18~39:1~2.
[0026] The present invention also provides a method for preparing multi-level composite micro-nano particles with wide spectrum control performance as described in any of the above items, firstly, the surface of the core particles is pretreated, and then the pretreated core particles are added to a silane coupling agent solution, stirred at 25-60°C for 2-10 hours for reaction, and ultrasonicated for 1-5 hours during the stirring process, and immediately after the reaction, the unreacted or excess silane coupling agent is removed by washing, and then the particles are placed in a vacuum oven at 60-80°C for full drying to obtain core particles modified by silane coupling agent, and the appropriate silane coupling agent is determined according to the type of silane coupling agent. The temperature and reaction time are controlled, and the stirring and ultrasonic time are controlled to ensure that the core particles are well dispersed in the silane coupling agent solution to avoid aggregation between the particles. Finally, a sol-gel method, a co-precipitation method, a hydrothermal method or an impregnation method are used to form an intermediate layer of nanoparticles on the surface of the core particles to obtain multi-level composite micro-nanoparticles with wide-spectrum regulation performance. Based on the grafted part of the silane coupling agent, the intermediate layer of nanoparticles is formed on the surface of the core particles after adsorbing metal ions, and the remaining part of the silane coupling agent forms an organic outer layer, which enhances the overall stability of the organic-inorganic interface.
[0027] The reason why the present invention pre-grafts the silane coupling agent onto the core particles is:
[0028] (1) The grafted silane coupling agent acts as a template or interface layer for the deposition of metal oxide nanoparticles, adsorbing the metal ions in the intermediate layer, so that the intermediate layer particles are tightly combined with the core particles. However, if the silane coupling agent is grafted on the surface of the intermediate layer particles, there will be problems of uneven coverage and reduced grafting efficiency;
[0029] (2) After the silane coupling agent is pre-grafted onto the core particles, the presence of the silane coupling agent can limit the growth space of the metal oxide, reduce the agglomeration between the metal oxide nanoparticles, and make them tend to grow uniformly into nanoparticles, rather than layered wrapping or growing into larger micron-sized particles, thereby improving the uniformity and stability of the material;
[0030] (3) By controlling the reaction conditions (including metal ion concentration, reaction time and reaction temperature), retaining part of the silane coupling agent outside the intermediate layer can not only protect the metal oxide nanoparticles from oxidation and environmental corrosion, but also enhance the dispersibility of the composite particles in the organic matrix and reduce agglomeration. Specifically:
[0031] The concentration of the precursor solution and metal ions directly affects the available amount and deposition rate of the metal ions. The initial concentration of the metal ions in the reaction solution is adjusted to keep it within a suitable range: a lower concentration of the precursor solution can reduce the reaction rate, so that the metal ions have enough time to diffuse to the hydrophilic sites and deposit, providing conditions for local coverage. By controlling the concentration, the metal ions can form a uniform and controllable nanoparticle deposition around the core particles, rather than quickly and massively covering the entire silane layer. A shorter reaction time can prevent the overgrowth of nanoparticles, ensuring that the metal oxide nanoparticles grow uniformly on the surface of the core particles, but not overgrow to completely cover all silane coupling agents; the reaction temperature is controlled within a suitable range, and the appropriate temperature is conducive to uniform deposition and the formation of fine particles. The specific reaction parameters vary depending on the preparation method. During the reaction, the slow addition of hydrolysis solvents, precipitants, and reducing agents can provide a balanced and slow growth environment, so that the metal ions have enough time to be directional deposited in the hydrophilic area without quickly covering the entire silane layer.
[0032] As the preferred technical solution:
[0033] The preparation method of the multi-level composite micro-nano particles with wide spectrum regulation performance as described above, the process of pretreating the surface of the core particles is: first, the core particles are dispersed in a mixed solution of water and ethanol, and ultrasonic cleaning is performed to remove organic matter, impurities, etc. on the surface to improve the surface cleanliness and activity, and then the cleaned core particles are dispersed in a 10% by mass hydrochloric acid solution, stirred at room temperature for 1~2 hours, and ultrasonically treated for 0.5~3 hours after stirring to achieve acid treatment of the titanium dioxide surface, and after filtering, it is repeatedly washed with deionized water until the pH value of the filtrate is 6~7, and dried in a vacuum oven at 60~80℃ for 24 hours.
[0034] In the method for preparing multi-level composite micro-nano particles with wide spectrum regulation performance as described above, the volume concentration of the silane coupling agent solution is 0.1-5%, and an appropriate amount and concentration of silane coupling agent is used to prevent excessive aggregation and ensure uniform grafting.
[0035] In the method for preparing multi-level composite micro-nano particles with wide spectrum control performance as described above, the mass ratio of the core particles to the silane coupling agent solution is 10-50:1, which is specifically adjusted within this range according to the core particle size and the molecular weight of the silane coupling agent.
[0036] The method for preparing multi-level composite micro-nano particles with wide spectrum regulation performance as described above, the process of forming intermediate layer nanoparticles on the surface of the core particles by the sol-gel method is as follows: first, a metal salt precursor (vanadium alkoxide, ethoxyvanadium, ethoxytungsten or tetraisopropoxyzirconium) is dispersed in ethanol, and ultrasonically stirred until completely dissolved to obtain a metal ion solution with a concentration of 0.05-1.0 mol / L; then, deionized water is added dropwise to the metal ion solution at a rate of 0.05-0.1 mL per minute under stirring conditions of a stirring rate of 400-800 rpm, and the molar ratio of metal ions to deionized water is 1:2-1:5. To prevent particle agglomeration, the reaction is continued to be stirred for 1-3 minutes after the addition is completed. h to form a metal sol; finally, the core particles modified by the silane coupling agent are added to the metal sol, the molar ratio of metal ions to core particles is 1:5~20, and the reducing agent (sodium borohydride or ascorbic acid) is added after stirring for 3~5 hours, and the molar ratio of the reducing agent to metal ions is 2~4:1. The stirring is continued to react, and after the reaction is completed, the particles are collected by filtration or centrifugation, and are repeatedly washed with deionized water and ethanol and placed in a vacuum oven at 60~80℃ for drying.
[0037] The method for preparing the multi-level composite micro-nano particles with wide spectrum control performance as described above, wherein the process of forming the intermediate layer nanoparticles on the surface of the core particles by the coprecipitation method is as follows: firstly, a metal salt precursor (vanadium nitrate, aluminum nitrate, magnesium nitrate, zirconium (IV) nitrate or iron nitrate) is dissolved in deionized water to obtain a metal ion solution with a concentration of 0.01-0.05 mol / L, and a precipitant (ammonia water or sodium hydroxide) is dissolved in deionized water to obtain a precipitant solution with a concentration of 0.1-0.5 mol / L; then, the core particles modified by the silane coupling agent are added to the metal ion solution, the molar ratio of the metal ions to the core particles is 1:5-10, and the mixture is stirred for 1-5 hours, and the mixture is stirred at a rate of 0.05-0.1 mol / L per minute under stirring conditions. The precipitant solution was added dropwise at a rate of 10 mL, and the change in pH value was detected at the same time. The pH value of the solution was controlled to be 8-10. The reaction was stirred continuously until the metal ions in the solution were completely precipitated. The end of the reaction was determined by the change in the color of the precipitate and the change in the transparency of the solution. Finally, after the reaction was completed, the precipitate was filtered and washed with deionized water to remove residual impurities and dissolved salts in the solution. The washed precipitate was then transferred to a vacuum oven at 60-80°C for drying.
[0038] The preparation method of the multi-level composite micro-nano particles with wide spectrum regulation performance as described above, the process of forming intermediate layer nanoparticles on the surface of the core particles by hydrothermal method is as follows: first, a metal salt precursor (vanadium acetate, aluminum acetate, magnesium acetate, zirconium acetate or iron acetate) is dissolved in deionized water to obtain a metal ion solution with a concentration of 0.1~0.5 mol / L; then the core particles modified by the silane coupling agent are added to the metal ion solution, the molar ratio of metal ions to core particles is 1:5~10, and stirred for 1~5 hours to obtain a mixed solution; finally, the mixed solution is transferred to a hydrothermal reactor with a PTFE inner core, sealed and placed in an oven at 100~180℃ for reaction for 12~24 hours; after the reaction is completed, the hydrothermal reactor is taken out, cooled and filtered, and the residual impurities and unreacted precursors in the solution are repeatedly washed with deionized water to remove them, and then the washed particles are placed in a vacuum oven at 60~80℃ for drying.
[0039] The method for preparing multi-level composite micro-nano particles with wide spectrum regulation performance as described above, the process of forming intermediate layer nanoparticles on the surface of the core particles by impregnation method is as follows: first, a metal salt precursor (sodium tungstate, barium tungstate or aluminum triisopropoxide) is dissolved in deionized water to obtain a metal ion solution with a concentration of 0.01-0.05 mol / L; then the core particles modified by silane coupling agent are added to the metal ion solution, the molar ratio of metal ions to core particles is 1:5-10, and stirred for 1-5 hours to allow the metal ions to be adsorbed on the surface of the core particles. After the stirring, the core particles modified by silane coupling agent are immersed in the metal ion solution for 1-24 hours to allow the metal ions to be fully adsorbed on the surface of the core particles, so as to form uniform intermediate layer nanoparticles in the subsequent heating and treatment steps; finally, the impregnated solution is heated in a water bath to 60-80°C, and is successively distilled and filtered and then repeatedly washed with deionized water to remove the remaining metal salts and impurities in the solution, and then the washed particles are placed in a vacuum oven at 60-80°C for drying.
[0040] After the above four methods form intermediate layer nanoparticles on the surface of the inner core particles, the crystallization and stabilization of the metal oxide can be promoted by further low-temperature heat treatment. Specifically, the dried composite particles are placed in a crucible, transferred to a tubular furnace, and protected by nitrogen. The particles are calcined at 300-500°C for 2-4 hours to improve the crystallinity and adhesion stability of the metal oxide.
[0041] The present invention also provides an application of the multi-level composite micro-nano particles with wide spectrum control performance as described in any one of the above items, characterized in that: after the multi-level composite micro-nano particles with wide spectrum control performance are uniformly mixed with a polymer masterbatch and dried, a fiber with radiative cooling properties is prepared by a melt spinning process;
[0042] The polymer is polyester (PET), nylon 6 (PA6) or polypropylene (PP).
[0043] As the preferred technical solution:
[0044] As mentioned above, the application of multi-level composite micro-nano particles with wide spectrum regulation performance, in the polymer fiber with radiation cooling characteristics, the addition amount of multi-level composite micro-nano particles with wide spectrum regulation performance is 0.05~10%; the fiber with radiation cooling characteristics has a sunlight (0.2~2.5μm) reflectivity of 70~99%, and a mid-to-far infrared (2.5~15μm) emissivity of 65~99%. The corresponding relationship between the specific addition amount and the sunlight (0.2~2.5μm) reflectivity and mid-to-far infrared (2.5~15μm) emissivity is shown in the following table:
[0045] Addition ratio (mass fraction) Sunlight (0.2~2.5 μm) reflectivity Mid- and far-infrared (2.5~15 μm) emissivity 0.05~1.0% 70~99% 65~80% 1.0~2.0% 85~99% 75~90% 2.0~5.0% 90~99% 85~99%
[0046] Principle of the invention:
[0047] The multi-level composite micro-nano particles of the present invention have wide spectrum regulation performance, including three parts: core particles, middle layer particles and outer layer organic matter. By regulating the particle size and distribution of the core particles, high reflection of sunlight in the range of 0.2~2.5μm can be achieved. At the same time, the core particles have a higher refractive index, which is significantly different from the surrounding medium (usually air or polymer matrix). When light enters another medium from one medium, the light is strongly reflected due to the refractive index difference. In addition, when multiple high-refractive index particles are stacked or form a multi-layer structure, the light is repeatedly reflected and interfered between these layers, increasing the reflection efficiency.
[0048] The middle layer is composed of oxide nanoparticles with high emissivity (such as at least one of vanadium oxide, tungsten oxide, aluminum oxide, magnesium oxide, zirconium oxide, and iron oxide). The vibration modes of atoms and molecules of these materials match the electromagnetic waves in the mid- and far-infrared bands, allowing these materials to effectively couple with infrared radiation, thereby increasing the emission efficiency, especially in the atmospheric window range of 8 to 13 μm, which can efficiently dissipate the heat of objects into outer space in the form of radiation, achieving the effect of cooling objects. Moreover, due to the nano size, it has a rich specific surface area and can emit and absorb thermal radiation more effectively.
[0049] The outer organic matter is a silane coupling agent. The structure of these compounds contains organic functional groups that can combine with inorganic materials, and organic end groups that can interact with the organic polymer matrix. This dual functionality enables the silane coupling agent to form a strong chemical bond at the inorganic / organic interface, improving the dispersibility of the nanoparticles in the polymer matrix. The organic functional groups in the outer layer can prevent the agglomeration of particles through electrostatic effects and steric hindrance effects, thereby improving the dispersibility of particles in the polymer. The functional groups such as hydroxyl and amino groups on the outside can form hydrogen bonds and other interactions with the polymer matrix, thereby achieving more uniform dispersion and stability.
[0050] Multi-level composite micro-nano particles have good radiation cooling effect. Adding them to the polymer matrix can achieve radiation cooling performance in a wide band range. It has the following advantages:
[0051] (1) High sunlight reflectivity:
[0052] The materials based on the core particles are titanium dioxide, zinc oxide or silicon dioxide, with a particle size range of 50~500nm. They can efficiently reflect solar radiation (0.2~2.5μm) with a reflectivity of more than 90%, significantly reducing the solar heat absorbed by the material, thereby reducing the fiber surface temperature and achieving a shading and cooling effect.
[0053] (2) High emissivity in the mid- and far-infrared bands:
[0054] The middle layer particles are at least one of vanadium oxide, tungsten oxide, aluminum oxide, magnesium oxide, zirconium oxide, and iron oxide nanoparticles, which provide efficient emission of thermal radiation under the atmospheric window (2.5~25 μm). By optimizing the size (particle size range 10~100 nm) and proportion of these nanoparticles, the radiation emissivity reaches more than 70%, realizing the daytime radiation cooling function, improving the infrared radiation efficiency of the fiber, and increasing the heat dissipation rate of the human body.
[0055] (3) Excellent dispersion performance and composite stability:
[0056] The outer layer silane coupling agent and its terminal functional groups (hydroxyl, amino, carboxyl, etc.) can form hydrogen bonds, van der Waals forces and other interactions with the polymer matrix, improve the dispersibility and stability of the composite particles in the matrix, ensure the uniform distribution of functional materials in the matrix, and thus achieve the desired excellent optical and thermal properties.
[0057] (4) Multifunctional composite properties:
[0058] The multi-level composite core-shell particles are combined with the polymer matrix, and the added composite particles achieve good functional performance at a mass ratio of 0.05-5% without affecting the basic mechanical properties of the material. The prepared functional fiber can effectively block solar radiation, and at the same time dissipate heat through mid- and far-infrared radiation, so that the fiber material remains cool in high-temperature outdoor environments. It has the dual effects of regulating anti-solar radiation and human radiation cooling, bringing a good sense of coolness, and is suitable for outdoor clothing and building materials.
[0059] Beneficial effects:
[0060] (1) The multi-level composite micro-nano particles of the present invention with wide spectrum control performance can simultaneously achieve high reflection in the solar spectrum band (0.3-2.5 μm) and high emission in the mid-infrared band (2.5-25 μm), and have a good radiation cooling effect.
[0061] (2) The present invention provides a method for preparing multi-level composite micro-nano particles with wide spectrum control performance. By adjusting the particle size and distribution of the core particles, high reflection of sunlight in the range of 0.2 to 2.5 μm can be achieved; the middle layer particles can realize the daytime radiation cooling function, improve the infrared radiation efficiency of the fiber, and increase the heat dissipation rate of the human body; in addition, the outer layer silane coupling agent includes two types of silane coupling agents grafted with hydrophilic and hydrophobic functional groups, which can achieve good dispersibility and interface compatibility of the particles in different matrices;
[0062] (3) The present invention provides an application of multi-level composite micro-nano particles with wide spectrum regulation performance. The multi-level composite core-shell particles are combined with a polymer matrix to prepare functional fibers that can effectively block solar radiation and dissipate heat through mid- and far-infrared radiation, so that the fiber material remains cool even in high-temperature outdoor environments. It has the dual regulation effects of anti-solar radiation and human body radiation cooling, bringing a good sense of coolness, and is suitable for use in outdoor clothing and building materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0063] Figure 1 This is a SEM image of the OH-V2O5@TiO2 multi-level composite micro-nano particles of Example 1;
[0064] Figure 2 Schematic diagram of multi-level composite micro-nano particles;
[0065] Figure 3 Schematic diagram of the radiation cooling effect of multi-level composite micro-nano particles;
[0066] Figure 4 The uniform distribution of multi-composite micro-nano particles in the fiber matrix;
[0067] Among them, 1-inner core particles; 2-middle layer particles; 3-outer layer organic matter. DETAILED DESCRIPTION
[0068] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.
[0069] The test methods involved in the performance indicators of the present invention are as follows:
[0070] Solar reflectivity: The test was conducted using a UV-visible near-infrared spectrophotometer (ThermoFisher Evolution220) equipped with an integrating sphere. The test range was 280-2500 nm.
[0071] Mid- and far-infrared emissivity: Fourier transform infrared spectrometer (Bruker Vertex 70v) equipped with an integrating sphere, test range: 2.5~25μm, test emissivity.
[0072] Example 1
[0073] A method for preparing multi-level composite micro-nano particles with wide spectrum control performance, the specific steps are as follows:
[0074] (1) Pretreatment of the surface of the core particles:
[0075] First, the core particles are dispersed in a mixed solution of water and ethanol, and ultrasonically cleaned. Then, the cleaned core particles are dispersed in a 10% by mass hydrochloric acid solution, stirred at room temperature for 1 hour, and ultrasonically treated for 3 hours after the stirring is completed. After filtering, the core particles are repeatedly washed with deionized water until the pH value of the filtrate is 6, and dried in a vacuum oven at 60°C for 24 hours to obtain the pretreated core particles.
[0076] The core particles are titanium dioxide with a particle size range of 200-500 nm; in the mixed solution of water and ethanol, the volume ratio of water to ethanol is 1:1;
[0077] (2) adding the pretreated core particles to an anhydrous ethanol solution of a silane coupling agent having a volume concentration of 0.1%, stirring at 25° C. for 4 h to react, and ultrasonicating for 2 h during the stirring process to obtain core particles modified with a silane coupling agent;
[0078] Among them, the terminal functional groups of a part of the silane coupling agents are hydrophilic functional groups, and the terminal functional groups of the other part of the silane coupling agents are hydrophobic functional groups; the silane coupling agent with a hydrophilic functional group at the terminal is a mixture of 3-aminopropyltriethoxysilane (APTES), γ-methacryloxypropyltrimethoxysilane (MPS) and 3-mercaptopropyltrimethoxysilane (MPTMS) in a molar ratio of 1:1:1; the silane coupling agent with a hydrophobic functional group at the terminal is vinyltriethoxysilane; the molar ratio of the silane coupling agent with a hydrophilic functional group at the terminal to the silane coupling agent with a hydrophobic functional group at the terminal is 2:1;
[0079] (3) Using the sol-gel method to form intermediate layer nanoparticles on the surface of the core particles:
[0080] (3.1) dispersing ethoxyvanadium in ethanol and stirring by ultrasonic until completely dissolved to obtain a metal ion (vanadium ion) solution with a concentration of 0.05 mol / L;
[0081] (3.2) adding deionized water to the metal ion solution at a rate of 0.05 mL / min under stirring at a stirring rate of 400 rpm, wherein the molar ratio of metal ions to deionized water is 1:2, and stirring is continued for 1 h after the addition is completed to form a metal sol;
[0082] (3.3) adding the core particles modified with the silane coupling agent in step (2) to the metal sol, with the molar ratio of metal ions to core particles being 1:20, stirring and reacting for 3 hours, adding a reducing agent (sodium borohydride), with the molar ratio of reducing agent to metal ions being 2:1, and continuing to stir and react. After the reaction is completed, filtering or centrifuging to collect the particles, repeatedly washing with deionized water and ethanol, and drying in a vacuum oven at 60°C to form intermediate layer nanoparticles, and finally preparing multi-level composite micro-nano particles with wide spectrum control performance;
[0083] Among them, the mass ratio of the inner core particles, the middle layer particles and the outer layer organic matter is 60:39:1; the outer layer organic matter is a silane coupling agent; the middle layer particles are vanadium oxide nanoparticles with a particle size range of 1~5nm.
[0084] like Figure 2 As shown, the finally prepared multi-level composite micro-nano particles (OH-V2O5@TiO2) with wide spectrum regulation performance include core particles 1, intermediate layer particles 2 and outer layer organic matter 3. The intermediate layer particles 2 grow uniformly on the surface of the core particles and are coated by the outer layer organic matter 3; the silane coupling agent with a hydrophobic terminal functional group is distributed between different intermediate layer particles 2.
[0085] Depend on Figure 1It can be seen that the size distribution of OH-V2O5@TiO2 multi-level composite micro-nano particles is between 300 and 800 nm, and there are densely distributed nanoparticles on the surface of the particles, which are evenly wrapped on the core particles.
[0086] like Figure 3 As shown, it is a schematic diagram of the ability of multi-level composite micro-nano particles to reflect sunlight (ultraviolet-visible-near infrared), radiate heat (mid-infrared-far infrared), and achieve interface compatibility with the matrix by surface functional groups, demonstrating the wide-spectrum regulation performance of multi-level composite micro-nano particles and their good compatibility with the matrix as functional particles.
[0087] Example 2
[0088] A method for preparing multi-level composite micro-nano particles with wide spectrum control performance, the specific steps are as follows:
[0089] (1) Pretreatment of the surface of the core particles:
[0090] First, the core particles are dispersed in a mixed solution of water and ethanol, and ultrasonically cleaned. Then, the cleaned core particles are dispersed in a 10% by mass hydrochloric acid solution, stirred at room temperature for 2 hours, and ultrasonically treated for 0.5 hours after stirring. After filtering, the core particles are repeatedly washed with deionized water until the pH value of the filtrate is 7, and dried in a vacuum oven at 80°C for 24 hours to obtain the pretreated core particles.
[0091] The core particles are titanium dioxide with a particle size range of 50-200 nm; the volume ratio of water to ethanol in the mixed solution of water and ethanol is 1:3;
[0092] (2) adding the pretreated core particles to an anhydrous ethanol solution of a silane coupling agent having a volume concentration of 5%, stirring at 60° C. for 10 h to react, and ultrasonicating for 5 h during the stirring process to obtain core particles modified with a silane coupling agent;
[0093] Among them, the terminal functional groups of a part of the silane coupling agents are hydrophilic functional groups, and the terminal functional groups of the other part of the silane coupling agents are hydrophobic functional groups; the silane coupling agent with a hydrophilic terminal functional group is a mixture of 3-aminopropyltriethoxysilane (APTES), aminopropyltrimethoxysilane (APTMS), γ-methacryloxypropyltrimethoxysilane (MPS) and 3-mercaptopropyltrimethoxysilane (MPTMS) in a molar ratio of 1:1:1:1; the silane coupling agent with a hydrophobic terminal functional group is vinyltriethoxysilane; the molar ratio of the silane coupling agent with a hydrophilic terminal functional group to the silane coupling agent with a hydrophobic terminal functional group is 1:1;
[0094] (3) Using the sol-gel method to form intermediate layer nanoparticles on the surface of the core particles:
[0095] (3.1) Disperse ethoxytungsten in ethanol and stir by ultrasonic until it is completely dissolved to obtain a metal ion (tungsten ion) solution with a concentration of 0.5 mol / L;
[0096] (3.2) adding deionized water to the metal ion solution at a rate of 0.1 mL / min under stirring at a stirring rate of 800 rpm, wherein the molar ratio of metal ions to deionized water is 1:5, and continuing to stir and react for 3 h to form a metal sol;
[0097] (3.3) adding the core particles modified with the silane coupling agent in step (2) to the metal sol, with the molar ratio of metal ions to core particles being 1:5, stirring and reacting for 5 hours, adding a reducing agent (ascorbic acid), with the molar ratio of reducing agent to metal ions being 3:1, and continuing to stir and react. After the reaction is completed, filtering or centrifuging to collect the particles, repeatedly washing with deionized water and ethanol, and drying in a vacuum oven at 80°C to form intermediate layer nanoparticles, and finally preparing multi-level composite micro-nano particles with wide spectrum control performance;
[0098] Among them, the mass ratio of the inner core particles, the middle layer particles and the outer layer organic matter is 80:18:2; the outer layer organic matter is a silane coupling agent; the middle layer particles are tungsten oxide nanoparticles with a particle size range of 16~20nm.
[0099] The finally obtained multi-level composite micro-nano particles with wide-spectrum regulation performance include core particles, middle layer particles and outer layer organic matter. The middle layer particles grow evenly on the surface of the core particles and are coated by the outer layer organic matter; the silane coupling agent with a hydrophobic terminal functional group is distributed between different middle layer particles.
[0100] Example 3
[0101] A method for preparing multi-level composite micro-nano particles with wide spectrum control performance, the specific steps are as follows:
[0102] (1) Pretreatment of the surface of the core particles:
[0103] First, the core particles were dispersed in a mixed solution of water and ethanol, and ultrasonically cleaned. Then, the cleaned core particles were dispersed in a 10% by mass hydrochloric acid solution, stirred at room temperature for 1 hour, and ultrasonically treated for 0.5 hours after stirring. After filtering, the core particles were repeatedly washed with deionized water until the pH value of the filtrate was 7, and dried in a vacuum oven at 60°C for 24 hours to obtain the pretreated core particles.
[0104] The core particles are titanium dioxide with a particle size range of 50 to 200 nm; in the mixed solution of water and ethanol, the volume ratio of water to ethanol is 1:1;
[0105] (2) adding the pretreated core particles to an anhydrous ethanol solution of a silane coupling agent having a volume concentration of 0.1%, stirring at 25° C. for 2 h to react, and ultrasonicating for 5 h during the stirring process to obtain core particles modified with a silane coupling agent;
[0106] Among them, the terminal functional groups of a part of the silane coupling agents are hydrophilic functional groups, and the terminal functional groups of the other part of the silane coupling agents are hydrophobic functional groups; the silane coupling agent with a hydrophilic terminal functional group is 3-aminopropyltriethoxysilane (APTES); the silane coupling agent with a hydrophobic terminal functional group is vinyltriethoxysilane; the molar ratio of the silane coupling agent with a hydrophilic terminal functional group to the silane coupling agent with a hydrophobic terminal functional group is 2:1;
[0107] (3) Using the co-precipitation method to form intermediate layer nanoparticles on the surface of the core particles:
[0108] (3.1) dissolving aluminum nitrate nonahydrate in deionized water to obtain a metal ion (aluminum ion) solution with a concentration of 0.01 mol / L, and dissolving a precipitant (ammonia water) in deionized water to obtain a precipitant solution with a concentration of 0.1 mol / L;
[0109] (3.2) Then, the core particles modified with silane coupling agent were added to the metal ion solution, with the molar ratio of metal ions to core particles being 1:5. The mixture was stirred for 1 hour. Under stirring conditions, the precipitant solution was added dropwise at a rate of 0.1 mL per minute. The pH value was detected at the same time. The pH value of the solution was controlled to be 8. The reaction was stirred continuously until the metal ions in the solution were completely precipitated. The reaction was concluded by the change in the color of the precipitate and the change in the transparency of the solution.
[0110] (3.3) After the reaction is completed, the precipitate is filtered and washed with deionized water. The washed precipitate is then transferred to a 60°C vacuum oven and dried to obtain intermediate layer nanoparticles, thereby finally obtaining multi-level composite micro-nanoparticles with wide spectrum control performance.
[0111] Among them, the mass ratio of the inner core particles, the middle layer particles and the outer layer organic matter is 70:29:1; the outer layer organic matter is a silane coupling agent; the middle layer particles are aluminum oxide with a particle size range of 1~5nm.
[0112] The finally obtained multi-level composite micro-nano particles with wide-spectrum regulation performance include core particles, middle layer particles and outer layer organic matter. The middle layer particles grow evenly on the surface of the core particles and are coated by the outer layer organic matter; the silane coupling agent with a hydrophobic terminal functional group is distributed between different middle layer particles.
[0113] Example 4
[0114] A method for preparing multi-level composite micro-nano particles with wide spectrum control performance, the specific steps are as follows:
[0115] (1) Pretreatment of the surface of the core particles:
[0116] First, the core particles are dispersed in a mixed solution of water and ethanol, and ultrasonically cleaned. Then, the cleaned core particles are dispersed in a 10% by mass hydrochloric acid solution, stirred at room temperature for 2 hours, and ultrasonically treated for 3 hours after stirring. After filtering, the core particles are repeatedly washed with deionized water until the pH value of the filtrate is 7, and dried in a vacuum oven at 80°C for 24 hours to obtain the pretreated core particles.
[0117] The core particles are silicon dioxide with a particle size range of 200-500 nm; in the mixed solution of water and ethanol, the volume ratio of water to ethanol is 1:4;
[0118] (2) adding the pretreated core particles to an anhydrous ethanol solution of a silane coupling agent having a volume concentration of 5%, stirring at 60° C. for 10 h to react, and ultrasonicating for 5 h during the stirring process to obtain core particles modified with a silane coupling agent;
[0119] Among them, the terminal functional groups of a part of the silane coupling agents are hydrophilic functional groups, and the terminal functional groups of the other part of the silane coupling agents are hydrophobic functional groups; the silane coupling agent with a hydrophilic functional group as the terminal functional group is a mixture of γ-methacryloxypropyltrimethoxysilane (MPS), 3-carboxyethyltriethoxysilane (CTES) and 3-mercaptopropyltrimethoxysilane (MPTMS) in a molar ratio of 1:1:1; the silane coupling agent with a hydrophobic functional group as the terminal functional group is vinyltriethoxysilane; the molar ratio of the silane coupling agent with a hydrophilic functional group as the terminal functional group to the silane coupling agent with a hydrophobic functional group as the terminal functional group is 1:1;
[0120] (3) Using the co-precipitation method to form intermediate layer nanoparticles on the surface of the core particles:
[0121] (3.1) dissolving ferric nitrate nonahydrate in deionized water to obtain a metal ion (iron ion) solution with a concentration of 0.05 mol / L, and dissolving a precipitant (sodium hydroxide) in deionized water to obtain a precipitant solution with a concentration of 0.5 mol / L;
[0122] (3.2) Then, the core particles modified with silane coupling agent were added to the metal ion solution, with the molar ratio of metal ions to core particles being 1:10. The mixture was stirred for 5 h. Under stirring conditions, the precipitant solution was added dropwise at a rate of 0.1 mL per minute. The pH value was detected at the same time. The pH value of the solution was controlled to be 10. The reaction was stirred continuously until the metal ions in the solution were completely precipitated. The reaction was concluded by the change in the color of the precipitate and the change in the transparency of the solution.
[0123] (3.3) After the reaction is completed, the precipitate is filtered and washed with deionized water. The washed precipitate is then transferred to a vacuum oven at 80°C and dried to obtain intermediate layer nanoparticles, thereby finally obtaining multi-level composite micro-nanoparticles with wide spectrum control performance.
[0124] Among them, the mass ratio of the inner core particles, the middle layer particles and the outer layer organic matter is 75:24:1; the outer layer organic matter is a silane coupling agent; the middle layer particles are ferric oxide with a particle size range of 10~15nm.
[0125] The finally obtained multi-level composite micro-nano particles with wide-spectrum regulation performance include core particles, middle layer particles and outer layer organic matter. The middle layer particles grow evenly on the surface of the core particles and are coated by the outer layer organic matter; the silane coupling agent with a hydrophobic terminal functional group is distributed between different middle layer particles.
[0126] Example 5
[0127] A method for preparing multi-level composite micro-nano particles with wide spectrum control performance, the specific steps are as follows:
[0128] (1) Pretreatment of the surface of the core particles:
[0129] Firstly, the core particles are dispersed in a mixed solution of water and ethanol, and ultrasonically cleaned. Then, the cleaned core particles are dispersed in a 10% by mass hydrochloric acid solution, stirred at room temperature for 1 hour, and ultrasonically treated for 1 hour after stirring. After filtering, the core particles are repeatedly washed with deionized water until the pH value of the filtrate is 6, and dried in a vacuum oven at 60°C for 24 hours to obtain the pretreated core particles.
[0130] The core particles are titanium dioxide with a particle size range of 50-200 nm; in the mixed solution of water and ethanol, the volume ratio of water to ethanol is 1:1;
[0131] (2) adding the pretreated core particles to an anhydrous ethanol solution of a silane coupling agent having a volume concentration of 0.1%, stirring at 50° C. for 5 h to react, and ultrasonicating for 1 h during the stirring process to obtain core particles modified with a silane coupling agent;
[0132] Among them, the terminal functional groups of a part of the silane coupling agents are hydrophilic functional groups, and the terminal functional groups of the other part of the silane coupling agents are hydrophobic functional groups; the silane coupling agent with a hydrophilic terminal functional group is 3-aminopropyltriethoxysilane (APTES); the silane coupling agent with a hydrophobic terminal functional group is vinyltriethoxysilane; the molar ratio of the silane coupling agent with a hydrophilic terminal functional group to the silane coupling agent with a hydrophobic terminal functional group is 1:1;
[0133] (3) Using the hydrothermal method to form intermediate layer nanoparticles on the surface of the core particles:
[0134] (3.1) First, magnesium acetate tetrahydrate is dissolved in deionized water to obtain a metal ion (magnesium ion) solution with a concentration of 0.1 mol / L;
[0135] (3.2) Then, the surface pretreated core particles are added to the metal ion solution, the molar ratio of metal ions to core particles is 1:5, and stirred for 5 hours to obtain a mixed solution;
[0136] (3.3) The mixed solution was transferred to a hydrothermal reactor with a PTFE inner core, sealed and placed in a 100°C oven for reaction for 20 hours; after the reaction was completed, the hydrothermal reactor was taken out, cooled and filtered, and the washed particles were repeatedly washed with deionized water, and then placed in a vacuum oven at 80°C for drying, and finally multi-level composite micro-nano particles with wide spectrum control performance were obtained;
[0137] Among them, the mass ratio of the inner core particles, the middle layer particles and the outer layer organic matter is 60:39:1; the outer layer organic matter is a silane coupling agent; and the middle layer particles are magnesium oxide with a particle size range of 5 to 15 nm.
[0138] The finally obtained multi-level composite micro-nano particles with wide-spectrum regulation performance include core particles, middle layer particles and outer layer organic matter. The middle layer particles grow evenly on the surface of the core particles and are coated by the outer layer organic matter; the silane coupling agent with a hydrophobic terminal functional group is distributed between different middle layer particles.
[0139] Example 6
[0140] A method for preparing multi-level composite micro-nano particles with wide spectrum control performance, the specific steps are as follows:
[0141] (1) Pretreatment of the surface of the core particles:
[0142] First, the core particles are dispersed in a mixed solution of water and ethanol, and ultrasonically cleaned. Then, the cleaned core particles are dispersed in a 10% by mass hydrochloric acid solution, stirred at room temperature for 2 hours, and ultrasonically treated for 2 hours after stirring. After filtering, the core particles are repeatedly washed with deionized water until the pH value of the filtrate is 7, and dried in a vacuum oven at 80°C for 24 hours to obtain the pretreated core particles.
[0143] The core particles are zinc oxide with a particle size range of 200-500 nm; in the mixed solution of water and ethanol, the volume ratio of water to ethanol is 1:4;
[0144] (2) adding the pretreated core particles to an anhydrous ethanol solution of a silane coupling agent having a volume concentration of 3%, stirring at 40° C. for 10 h to react, and ultrasonicating for 5 h during the stirring process to obtain core particles modified with a silane coupling agent;
[0145] Among them, the terminal functional groups of some silane coupling agents are hydrophilic functional groups, and the terminal functional groups of other silane coupling agents are hydrophobic functional groups; the silane coupling agents with hydrophilic terminal functional groups are γ-methacryloxypropyltrimethoxysilane (MPS), 3-carboxyethyltriethoxysilane (CTES) and 3-mercaptopropyltrimethoxysilane (MPTMS) in a molar ratio of 1:1:1; the silane coupling agent with hydrophobic terminal functional groups is vinyltriethoxysilane; the molar ratio of the silane coupling agent with hydrophilic terminal functional groups to the silane coupling agent with hydrophobic terminal functional groups is 3:1;
[0146] (3) Using the hydrothermal method to form intermediate layer nanoparticles on the surface of the core particles:
[0147] (3.1) First, dissolve zirconium acetate dihydrate in deionized water to obtain a metal ion (zirconium ion) solution with a concentration of 0.5 mol / L;
[0148] (3.2) Then, the surface pretreated core particles are added to the metal ion solution, the molar ratio of metal ions to core particles is 1:7, and stirred for 5 hours to obtain a mixed solution;
[0149] (3.3) The mixed solution was transferred to a hydrothermal reactor with a PTFE inner core, sealed and placed in a 180°C oven for reaction for 12 hours; after the reaction was completed, the hydrothermal reactor was taken out, cooled and filtered, and the washed particles were repeatedly washed with deionized water, and then placed in a 60°C vacuum oven to dry, and finally multi-level composite micro-nano particles with wide spectrum control performance were obtained;
[0150] Among them, the mass ratio of the inner core particles, the middle layer particles and the outer layer organic matter is 80:18:2; the outer layer organic matter is a silane coupling agent; and the middle layer particles are zirconium oxide with a particle size range of 10~20nm.
[0151] The finally obtained multi-level composite micro-nano particles with wide-spectrum regulation performance include core particles, middle layer particles and outer layer organic matter. The middle layer particles grow evenly on the surface of the core particles and are coated by the outer layer organic matter; the silane coupling agent with a hydrophobic terminal functional group is distributed between different middle layer particles.
[0152] Example 7
[0153] A method for preparing multi-level composite micro-nano particles with wide spectrum control performance, the specific steps are as follows:
[0154] (1) Pretreatment of the surface of the core particles:
[0155] First, the core particles are dispersed in a mixed solution of water and ethanol, and ultrasonically cleaned. Then, the cleaned core particles are dispersed in a 10% by mass hydrochloric acid solution, stirred at room temperature for 2 hours, and ultrasonically treated for 3 hours after the stirring is completed. After filtering, the core particles are repeatedly washed with deionized water until the pH value of the filtrate is 7, and dried in a vacuum oven at 80°C for 24 hours to obtain the pretreated core particles.
[0156] The core particles are silicon dioxide with a particle size range of 50 to 200 nm; in the mixed solution of water and ethanol, the volume ratio of water to ethanol is 1:4;
[0157] (2) adding the pretreated core particles to an anhydrous ethanol solution of a silane coupling agent having a volume concentration of 5%, stirring at 60° C. for 10 h to react, and ultrasonicating for 5 h during the stirring process to obtain core particles modified with a silane coupling agent;
[0158] The terminal functional groups of a part of the silane coupling agents are hydrophilic functional groups, and the terminal functional groups of the other part of the silane coupling agents are hydrophobic functional groups; the silane coupling agent with a hydrophilic terminal functional group is a mixture of dihydroxydimethoxysilane (DHDMS) and γ-ethoxytrimethylolsilane (ETHOMS) in a molar ratio of 1:1; the silane coupling agent with a hydrophobic terminal functional group is vinyltriethoxysilane; the molar ratio of the silane coupling agent with a hydrophilic terminal functional group to the silane coupling agent with a hydrophobic terminal functional group is 3:1;
[0159] (3) Using the impregnation method to form an intermediate layer of nanoparticles on the surface of the core particles:
[0160] (3.1) dissolving aluminum triisopropoxide in deionized water to obtain a metal ion (aluminum ion) solution with a concentration of 0.5 mol / L;
[0161] (3.2) adding the modified core particles into a metal ion solution with a molar ratio of metal ions to core particles of 1:5, stirring for 5 hours, and then immersing the modified core particles in the metal ion solution for another 24 hours after stirring;
[0162] (3.3) The impregnated solution is heated to 80°C in a water bath, and then distilled and filtered, and then repeatedly washed with deionized water. The washed particles are then placed in a vacuum oven at 80°C to dry to obtain intermediate layer nanoparticles, and finally multi-level composite micro-nano particles with wide spectrum control performance are obtained;
[0163] Among them, the mass ratio of the inner core particles, the middle layer particles and the outer layer organic matter is 75:23:2; the outer layer organic matter is a silane coupling agent; and the middle layer particles are aluminum oxide with a particle size range of 10~20nm.
[0164] The finally obtained multi-level composite micro-nano particles with wide-spectrum regulation performance include core particles, middle layer particles and outer layer organic matter. The middle layer particles grow evenly on the surface of the core particles and are coated by the outer layer organic matter; the silane coupling agent with a hydrophobic terminal functional group is distributed between different middle layer particles.
[0165] Example 8
[0166] A method for preparing multi-level composite micro-nano particles with wide spectrum control performance, the specific steps are as follows:
[0167] (1) Pretreatment of the surface of the core particles:
[0168] First, the core particles were dispersed in a mixed solution of water and ethanol, and ultrasonically cleaned. Then, the cleaned core particles were dispersed in a 10% by mass hydrochloric acid solution, stirred at room temperature for 1 hour, and ultrasonically treated for 0.5 hours after stirring. After filtering, the core particles were repeatedly washed with deionized water until the pH value of the filtrate was 6, and dried in a vacuum oven at 60°C for 24 hours to obtain the pretreated core particles.
[0169] The core particles are zinc oxide with a particle size range of 50 to 200 nm; in the mixed solution of water and ethanol, the volume ratio of water to ethanol is 1:1;
[0170] (2) adding the pretreated core particles to an anhydrous ethanol solution of a silane coupling agent having a volume concentration of 0.1%, stirring at 40° C. for 5 h to react, and ultrasonicating for 2 h during the stirring process to obtain core particles modified with a silane coupling agent;
[0171] Among them, the terminal functional groups of a part of the silane coupling agents are hydrophilic functional groups, and the terminal functional groups of the other part of the silane coupling agents are hydrophobic functional groups; the silane coupling agent with a hydrophilic terminal functional group is 3-trihydroxypropyltrimethoxysilane (THPTMS); the silane coupling agent with a hydrophobic terminal functional group is vinyltriethoxysilane; the molar ratio of the silane coupling agent with a hydrophilic terminal functional group to the silane coupling agent with a hydrophobic terminal functional group is 1:1;
[0172] (3) Using the impregnation method to form an intermediate layer of nanoparticles on the surface of the core particles:
[0173] (3.1) Dissolve sodium tungstate in deionized water to obtain a metal ion (sodium ion) solution with a concentration of 0.1 mol / L;
[0174] (3.2) adding the modified core particles into a metal ion solution with a molar ratio of metal ions to core particles of 1:10, stirring for 5 hours, and then immersing the modified core particles in the metal ion solution for another 12 hours after stirring;
[0175] (3.3) The impregnated solution is heated to 60°C in a water bath, and then distilled and filtered, and then repeatedly washed with deionized water. The washed particles are then placed in a vacuum oven at 80°C to dry to obtain intermediate layer nanoparticles, and finally multi-level composite micro-nano particles with wide spectrum control performance are obtained;
[0176] Among them, the mass ratio of the inner core particles, the middle layer particles and the outer layer organic matter is 65:34:1; the outer layer organic matter is a silane coupling agent; and the middle layer particles are tungsten oxide with a particle size range of 1 to 10 nm.
[0177] The finally obtained multi-level composite micro-nano particles with wide-spectrum regulation performance include core particles, middle layer particles and outer layer organic matter. The middle layer particles grow evenly on the surface of the core particles and are coated by the outer layer organic matter; the silane coupling agent with a hydrophobic terminal functional group is distributed between different middle layer particles.
[0178] Example 9
[0179] An application of multi-level composite micro-nano particles with wide spectrum control performance, the specific steps are as follows:
[0180] (1) Preparation of raw materials:
[0181] The multi-level composite micro-nano particles with wide spectrum control performance of Example 1;
[0182] PET powder: obtained by crushing PET resin chips, with a particle size of 300~500μm; PET resin chips: manufacturer: Yizheng Chemical Fiber, brand: FG600;
[0183] (2) The multi-level composite micro-nano particles with wide spectrum control performance of Example 1 and PET powder were uniformly mixed and dried at 50° C., and then a polyester fiber with radiative cooling properties was prepared by a melt spinning process;
[0184] In the polyester fiber with radiative cooling properties, the addition amount of multi-level composite micro-nano particles with wide spectrum regulation performance is 5%.
[0185] The final polyester fiber with radiative cooling properties has a reflectivity of 95-99% in the solar band (280-2500 nm) and a mid-to-far infrared emissivity of 90-99%; the performance of the polyester fiber with radiative cooling properties meets the performance indicators in GB / T 14190-2017 "Test Method for Fiber-Grade Polyester Chips (PET)".
[0186] like Figure 4The figure shows a schematic diagram of the uniform distribution of multi-level composite micro-nano particles within the fiber, demonstrating that the multi-level composite micro-nano particles, as functional particles, have good compatibility with the matrix and achieve their uniform distribution in the matrix.
[0187] Example 10
[0188] An application of multi-level composite micro-nano particles with wide spectrum control performance, the specific steps are as follows:
[0189] (1) Preparation of raw materials:
[0190] The multi-level composite micro-nano particles with wide spectrum control performance of Example 2;
[0191] PET powder: obtained by crushing PET resin chips, with a particle size of 300~500μm; PET resin chips: manufacturer: Yizheng Chemical Fiber, brand: FG600;
[0192] (2) The multi-level composite micro-nano particles with wide spectrum control performance of Example 2 and PET powder were uniformly mixed and dried at 50° C., and then a polyester fiber with radiative cooling properties was prepared by a melt spinning process;
[0193] In the polyester fiber with radiative cooling properties, the addition amount of multi-level composite micro-nano particles with wide spectrum regulation performance is 0.05%.
[0194] The final polyester fiber with radiative cooling properties has a reflectivity of 70-80% in the solar band (280-2500 nm) and a mid-to-far infrared emissivity of 65-70%. The performance of the polyester fiber with radiative cooling properties meets the performance indicators in GB / T 14190-2017 "Test Method for Fiber-Grade Polyester Chips (PET)".
[0195] Embodiment 11
[0196] An application of multi-level composite micro-nano particles with wide spectrum control performance, the specific steps are as follows:
[0197] (1) Preparation of raw materials:
[0198] The multi-level composite micro-nano particles with wide spectrum control performance of Example 3;
[0199] PET powder: obtained by crushing PET resin chips, with a particle size of 300~500μm; PET resin chips: manufacturer: Yizheng Chemical Fiber, brand: FG600;
[0200] (2) The multi-level composite micro-nano particles with wide spectrum control performance of Example 3 and PET powder were uniformly mixed and dried at 50° C., and then a polyester fiber with radiative cooling properties was prepared by a melt spinning process;
[0201] In the polyester fiber with radiative cooling properties, the addition amount of multi-level composite micro-nano particles with wide spectrum regulation performance is 0.5%.
[0202] The final polyester fiber with radiative cooling properties has a reflectivity of 80-90% in the solar band (280-2500 nm) and a mid-to-far infrared emissivity of 70-75%. The performance of the polyester fiber with radiative cooling properties meets the performance indicators in GB / T 14190-2017 "Test Method for Fiber-Grade Polyester Chips (PET)".
[0203] Example 12
[0204] An application of multi-level composite micro-nano particles with wide spectrum control performance, the specific steps are as follows:
[0205] (1) Preparation of raw materials:
[0206] The multi-level composite micro-nano particles with wide spectrum control performance of Example 4;
[0207] PET powder: obtained by crushing PET resin chips, with a particle size of 300~500μm; PET resin chips: manufacturer: Yizheng Chemical Fiber, brand: FG600;
[0208] (2) The multi-level composite micro-nano particles with wide spectrum control performance of Example 4 and PET powder were uniformly mixed and dried at 50° C., and then a polyester fiber with radiative cooling properties was prepared by a melt spinning process;
[0209] In the polyester fiber with radiative cooling properties, the addition amount of multi-level composite micro-nano particles with wide spectrum regulation performance is 1%.
[0210] The final polyester fiber with radiative cooling properties has a reflectivity of 90-99% in the solar band (280-2500 nm) and a mid-to-far infrared emissivity of 75-80%. The performance of the polyester fiber with radiative cooling properties meets the performance indicators in GB / T 14190-2017 "Test Method for Fiber-Grade Polyester Chips (PET)".
[0211] Example 13
[0212] An application of multi-level composite micro-nano particles with wide spectrum control performance, the specific steps are as follows:
[0213] (1) Preparation of raw materials:
[0214] The multi-level composite micro-nano particles with wide spectrum control performance of Example 5;
[0215] PET powder: obtained by crushing PET resin chips, with a particle size of 300~500μm; PET resin chips: manufacturer: Yizheng Chemical Fiber, brand: FG600;
[0216] (2) The multi-level composite micro-nano particles with wide spectrum control performance and PET powder of Example 5 were mixed uniformly by weight and dried at 50° C., and then a polyester fiber with radiative cooling properties was prepared by a melt spinning process;
[0217] In the polyester fiber with radiative cooling properties, the addition amount of multi-level composite micro-nano particles with wide spectrum regulation performance is 2%.
[0218] The final polyester fiber with radiative cooling properties has a reflectivity of 90-99% in the solar band (280-2500 nm) and a mid-to-far infrared emissivity of 85-95%. The performance of the polyester fiber with radiative cooling properties meets the performance indicators in GB / T 14190-2017 "Test Method for Fiber-Grade Polyester Chips (PET)".
[0219] Embodiment 14
[0220] The application of multi-level composite micro-nano particles with wide spectrum regulation performance has been carried out in the following specific steps:
[0221] (1) Preparation of raw materials:
[0222] The multi-level composite micro-nano particles with wide spectrum control performance of Example 6;
[0223] PET powder: obtained by crushing PET resin chips, with a particle size of 300~500μm; PET resin chips: manufacturer: Yizheng Chemical Fiber, brand: FG600;
[0224] (2) The multi-level composite micro-nano particles with wide spectrum control performance of Example 6 and PET powder were uniformly mixed and dried at 50° C., and then a polyester fiber with radiative cooling properties was prepared by a melt spinning process;
[0225] In the polyester fiber with radiative cooling properties, the addition amount of multi-level composite micro-nano particles with wide spectrum regulation performance is 3%.
[0226] The final polyester fiber with radiative cooling properties has a reflectivity of 90-95% in the solar band (280-2500 nm) and a mid-to-far infrared emissivity of 85-95%. The performance of the polyester fiber with radiative cooling properties meets the performance indicators in GB / T 14190-2017 "Test Method for Fiber-Grade Polyester Chips (PET)".
[0227] Embodiment 15
[0228] The application of multi-level composite micro-nano particles with wide spectrum regulation performance has been carried out in the following specific steps:
[0229] (1) Preparation of raw materials:
[0230] The multi-level composite micro-nano particles with wide spectrum control performance of Example 7;
[0231] PET powder: obtained by crushing PET resin chips, with a particle size of 300~500μm; PET resin chips: manufacturer: Yizheng Chemical Fiber, brand: FG600;
[0232] (2) The multi-level composite micro-nano particles with wide spectrum control performance of Example 7 and PET powder were uniformly mixed and dried at 50° C., and then a polyester fiber with radiative cooling properties was prepared by a melt spinning process;
[0233] In the polyester fiber with radiative cooling properties, the addition amount of multi-level composite micro-nano particles with wide spectrum regulation performance is 4%.
[0234] The final polyester fiber with radiative cooling properties has a reflectivity of 93-98% in the solar band (280-2500 nm) and a mid-infrared and far-infrared emissivity of 89-99%. The performance of the polyester fiber with radiative cooling properties meets the performance indicators in GB / T 14190-2017 "Test Method for Fiber-Grade Polyester Chips (PET)".
[0235] Example 16
[0236] An application of multi-level composite micro-nano particles with wide spectrum control performance, the specific steps are as follows:
[0237] (1) Preparation of raw materials:
[0238] The multi-level composite micro-nano particles with wide spectrum control performance of Example 8;
[0239] PET powder: obtained by crushing PET resin chips, with a particle size of 300~500μm; PET resin chips: manufacturer: Yizheng Chemical Fiber, brand: FG600;
[0240] (2) The multi-level composite micro-nano particles with wide spectrum control performance of Example 8 and PET powder were uniformly mixed and dried at 50° C., and then a polyester fiber with radiative cooling properties was prepared by a melt spinning process;
[0241] In the polyester fiber with radiative cooling properties, the addition amount of multi-level composite micro-nano particles with wide spectrum regulation performance is 5%.
[0242] The final polyester fiber with radiative cooling properties has a reflectivity of 95-99% in the solar band (280-2500 nm) and a mid-to-far infrared emissivity of 90-99%; the performance of the polyester fiber with radiative cooling properties meets the performance indicators in GB / T 14190-2017 "Test Method for Fiber-Grade Polyester Chips (PET)".
[0243] Embodiment 17
[0244] An application of multi-level composite micro-nano particles with wide spectrum control performance, the specific steps are as follows:
[0245] (1) Preparation of raw materials:
[0246] The multi-level composite micro-nano particles with wide spectrum control performance of Example 2;
[0247] Nylon 6 (PA6) powder: obtained by crushing nylon 6 resin chips; PA6 resin chips: manufacturer: Sinopec Baling Petrochemical, model: YH800;
[0248] (2) adding the multi-level composite micro-nano particles with wide spectrum control performance of Example 2 and PA6 into a twin-screw extruder for melt blending and extrusion granulation to obtain PA6 masterbatch with radiative cooling properties, and then using the mixture of the PA6 masterbatch with radiative cooling properties and PA6 as raw material for melt blending and spinning to obtain PA6 fibers with radiative cooling properties;
[0249] In the PA6 fiber with radiative cooling properties, the addition amount of multi-level composite micro-nano particles with wide spectrum regulation performance is 5%.
[0250] The final PA6 fiber with radiative cooling properties has a reflectivity of 75~85% in the solar band (280~2500 nm) and a mid-to-far infrared emissivity of 80~90%; the performance of PA6 chips and fibers with radiative cooling properties meets the performance indicators in GB / T38138-2019 "Test method for fiber-grade polycaprolactam (PA6) chips" and GB / T 6509-2005 "Determination method for the content of low molecular weight substances in polycaprolactam chips and fibers".
[0251] Embodiment 18
[0252] An application of multi-level composite micro-nano particles with wide spectrum control performance, the specific steps are as follows:
[0253] (1) Preparation of raw materials:
[0254] The multi-level composite micro-nano particles with wide spectrum control performance of Example 7;
[0255] Nylon 6 (PA6) powder: obtained by crushing nylon 6 resin chips; PA6 resin chips: manufacturer: Sinopec Baling Petrochemical, model: YH800;
[0256] (2) adding the multi-level composite micro-nano particles with wide spectrum control performance of Example 7 and PA6 into a twin-screw extruder for melt blending and extrusion granulation to obtain PA6 masterbatch with radiative cooling properties, and then using the mixture of the PA6 masterbatch with radiative cooling properties and PA6 as a raw material for melt blending and spinning to obtain PA6 fibers with radiative cooling properties;
[0257] In the PA6 fiber with radiative cooling properties, the addition amount of multi-level composite micro-nano particles with wide spectrum regulation performance is 10%.
[0258] The final PA6 fiber with radiative cooling properties has a reflectivity of 80~90% in the solar band (280~2500 nm) and a mid-infrared and far-infrared emissivity of 85~95%; the performance of PA6 chips and fibers with radiative cooling properties meets the performance indicators in GB / T38138-2019 "Test method for fiber-grade polycaprolactam (PA6) chips" and GB / T 6509-2005 "Determination method for the content of low molecular weight substances in polycaprolactam chips and fibers".
[0259] Embodiment 19
[0260] An application of multi-level composite micro-nano particles with wide spectrum control performance, the specific steps are as follows:
[0261] (1) Preparation of raw materials:
[0262] The multi-level composite micro-nano particles with wide spectrum control performance of Example 2;
[0263] Polypropylene powder: obtained by crushing polypropylene (PP) resin chips; Polypropylene resin chips: manufacturer: Yangzi Petrochemical, model: F401;
[0264] (2) adding the multi-level composite micro-nano particles with wide spectrum control performance of Example 2 and PP powder into a twin-screw extruder for melt blending and extrusion granulation to obtain PP masterbatch with radiative cooling properties, and then using the mixture of the PP masterbatch with radiative cooling properties and PP as raw materials for melt blending and spinning to obtain PP fibers with radiative cooling properties;
[0265] In the PP fiber with radiative cooling properties, the addition amount of multi-level composite micro-nano particles with wide spectrum regulation performance is 5%.
[0266] The final PP fiber with radiative cooling properties has a reflectivity of 70% to 80% in the solar band (280-2500 nm) and a mid-to-far infrared emissivity of 80% to 90%. The performance of the PP resin and fiber with radiative cooling properties meets the performance indicators in GB / T12670-2008 "Polypropylene (PP) Resin" and FZ / T 01141-2017 "Determination Method for Inorganic Filler Content in Polypropylene Fibers and Products".
[0267] Embodiment 20
[0268] An application of multi-level composite micro-nano particles with wide spectrum control performance, the specific steps are as follows:
[0269] (1) Preparation of raw materials:
[0270] The multi-level composite micro-nano particles with wide spectrum control performance of Example 1;
[0271] Polypropylene powder: obtained by crushing polypropylene (PP) resin chips; Polypropylene resin chips: manufacturer: Yangzi Petrochemical, model: F401;
[0272] (2) adding the multi-level composite micro-nano particles with wide spectrum control performance of Example 1 and PP powder into a twin-screw extruder for melt blending and extrusion granulation to obtain PP masterbatch with radiative cooling properties, and then using the mixture of the PP masterbatch with radiative cooling properties and PP as raw materials for melt blending and spinning to obtain PP fibers with radiative cooling properties;
[0273] In the PP fiber with radiative cooling properties, the addition amount of multi-level composite micro-nano particles with wide spectrum regulation performance is 10%.
[0274] The final PP fiber with radiative cooling properties has a reflectivity of 80-90% in the solar band (280-2500 nm) and a mid-to-far infrared emissivity of 85-95%. The performance of the PP resin and fiber with radiative cooling properties meets the performance indicators in GB / T12670-2008 "Polypropylene (PP) Resin" and FZ / T 01141-2017 "Determination Method for Inorganic Filler Content in Polypropylene Fibers and Products".
Claims
1. Multi-level composite micro-nano particles with wide spectrum control performance, characterized by: It includes inner core particles, middle layer particles and outer layer organic matter, wherein the middle layer particles grow evenly on the surface of the inner core particles and are covered by the outer layer organic matter; The inner core particles are inorganic particles A with a particle size range of 50-500 nm, the middle layer particles are inorganic particles B with a particle size range of 1-20 nm, and the outer layer organic matter is a silane coupling agent; The inorganic particles A are titanium dioxide, silicon dioxide or zinc oxide, and the inorganic particles B are one or more of vanadium oxide, tungsten oxide, aluminum oxide, magnesium oxide, zirconium oxide and iron oxide; The terminal functional groups of a part of silane coupling agents are hydrophilic functional groups, and the terminal functional groups of another part of silane coupling agents are hydrophobic functional groups; the silane coupling agents with hydrophobic terminal functional groups are distributed between different intermediate layer particles.
2. The multi-level composite micro-nano particles with wide spectrum control performance according to claim 1, characterized in that: The silane coupling agent having a hydrophilic terminal functional group is one or more of 3-aminopropyltriethoxysilane, aminopropyltrimethoxysilane, γ-methacryloxypropyltrimethoxysilane, 3-carboxyethyltriethoxysilane, 3-mercaptopropyltrimethoxysilane, 3-trihydroxypropyltrimethoxysilane, dihydroxydimethoxysilane and γ-ethoxytrihydroxymethylsilane, and the silane coupling agent having a hydrophobic terminal functional group is vinyltriethoxysilane.
3. The multi-level composite micro-nano particles with wide spectrum control performance according to claim 1, characterized in that: The particle size range of multi-level composite micro-nano particles with wide spectrum regulation performance is 100nm~3μm.
4. The multi-level composite micro-nano particles with wide spectrum control performance according to claim 1, characterized in that: The mass ratio of inner core particles, middle layer particles and outer layer organic matter is 60~80:18~39:1~2.
5. The method for preparing the multi-level composite micro-nano particles with wide spectrum control performance according to any one of claims 1 to 4, characterized in that: First, the surface of the core particles is pretreated, and then the pretreated core particles are added to a silane coupling agent solution, stirred at 25-60°C for 2-10 hours for reaction, and ultrasonicated for 1-5 hours during the stirring process to obtain core particles modified by the silane coupling agent. Finally, a sol-gel method, a co-precipitation method, a hydrothermal method or an impregnation method are used to form an intermediate layer of nanoparticles on the surface of the core particles to obtain multi-level composite micro-nano particles with wide spectrum regulation performance.
6. The method for preparing multi-level composite micro-nano particles with wide spectrum control performance according to claim 5, characterized in that: The process of pretreating the surface of the core particles is as follows: first, the core particles are dispersed in a mixed solution of water and ethanol, and ultrasonically cleaned. Then, the cleaned core particles are dispersed in a 10% by mass hydrochloric acid solution, stirred at room temperature for 1 to 2 hours, and ultrasonically treated for 0.5 to 3 hours after stirring. After filtering, the particles are repeatedly washed with deionized water until the pH value of the filtrate is 6 to 7, and dried in a vacuum oven at 60 to 80°C for 24 hours.
7. The method for preparing multi-level composite micro-nano particles with wide spectrum control performance according to claim 5, characterized in that: The volume concentration of the silane coupling agent solution is 0.1~5%.
8. The method for preparing multi-level composite micro-nano particles with wide spectrum control performance according to claim 5, characterized in that: The mass ratio of the core particles to the silane coupling agent solution is 10~50:
1.
9. The method for preparing multi-level composite micro-nano particles with wide spectrum control performance according to claim 5, characterized in that: The process of forming intermediate layer nanoparticles on the surface of the core particles by the sol-gel method is as follows: first, the metal salt precursor is dispersed in ethanol, ultrasonically stirred until completely dissolved, and a metal ion solution with a concentration of 0.05~1.0 mol / L is obtained; then, deionized water is added to the metal ion solution at a rate of 0.05~0.1 mL per minute under a stirring condition of a stirring rate of 400~800 rpm, and the molar ratio of metal ions to deionized water is 1:2~1:
5. After the addition is completed, stirring and reacting for 1~3 hours to form a metal sol; finally, the core particles modified by the silane coupling agent are added to the metal sol, and the molar ratio of metal ions to core particles is 1:5~20. After stirring and reacting for 3~5 hours, a reducing agent is added, and the molar ratio of the reducing agent to metal ions is 2~4:
1. Stirring and reacting are continued. After the reaction is completed, the particles are filtered or centrifuged to collect, and repeatedly washed with deionized water and ethanol and placed in a vacuum oven at 60~80°C for drying.
10. The method for preparing multi-level composite micro-nano particles with wide spectrum control performance according to claim 5, characterized in that: The process of forming intermediate layer nanoparticles on the surface of core particles by coprecipitation method is as follows: first, dissolve the metal salt precursor in deionized water to obtain a metal ion solution with a concentration of 0.01~0.05mol / L, and dissolve the precipitant in deionized water to obtain a precipitant solution with a concentration of 0.1~0.5mol / L; then add the core particles modified by silane coupling agent into the metal ion solution, the molar ratio of metal ions to core particles is 1:5~10, stir for 1~5h, and under stirring conditions, add the precipitant solution dropwise at a rate of 0.05-0.1 mL per minute, while detecting the change in pH value, controlling the solution pH=8~10, and continuously stirring the reaction until the metal ions in the solution are completely precipitated, and judging the end of the reaction by the change in precipitate color and solution transparency; finally, filter after the reaction is completed and wash the precipitate with deionized water, and then transfer the washed precipitate to a 60~80℃ vacuum oven for drying.
11. The method for preparing multi-level composite micro-nano particles with wide spectrum control performance according to claim 5, characterized in that: The process of forming intermediate layer nanoparticles on the surface of core particles by hydrothermal method is as follows: first, dissolve the metal salt precursor in deionized water to obtain a metal ion solution with a concentration of 0.1~0.5 mol / L; then add the core particles modified by silane coupling agent into the metal ion solution, the molar ratio of metal ions to core particles is 1:5~10, and stir for 1~5 hours to obtain a mixed solution; finally, transfer the mixed solution to a hydrothermal reactor with PTFE inner core, seal it and place it in a 100~180℃ oven to react for 12~24 hours; after the reaction is completed, take out the hydrothermal reactor, cool it and filter it, wash it repeatedly with deionized water, and then place the washed particles in a 60~80℃ vacuum oven to dry.
12. The method for preparing multi-level composite micro-nano particles with wide spectrum control performance according to claim 5, characterized in that: The process of forming intermediate layer nanoparticles on the surface of the core particles by the impregnation method is as follows: first, the metal salt precursor is dissolved in deionized water to obtain a metal ion solution with a concentration of 0.01~0.05mol / L; then the core particles modified by the silane coupling agent are added to the metal ion solution, the molar ratio of metal ions to core particles is 1:5~10, and stirred for 1~5h. After the stirring, the core particles modified by the silane coupling agent are immersed in the metal ion solution for 1~24h; finally, the immersed solution is heated in a water bath to 60~80℃, and then distilled and filtered in turn, and then repeatedly washed with deionized water, and then the washed particles are placed in a vacuum oven at 60~80℃ to dry.
13. The use of the multi-level composite micro-nano particles with wide spectrum control performance as claimed in any one of claims 1 to 4, characterized in that: The multi-level composite micro-nano particles with wide spectrum control performance are mixed evenly with the polymer masterbatch and dried, and then the fibers with radiative cooling properties are prepared by melt spinning process; The polymer is polyester, nylon 6 or polypropylene.
14. The use of the multi-level composite micro-nano particles with wide spectrum control performance according to claim 13, characterized in that: In the fiber with radiative cooling properties, the addition amount of multi-level composite micro-nano particles with wide-spectrum regulation performance is 0.05~10%; the solar reflectivity of the fiber with radiative cooling properties is 70~99%, and the mid- and far-infrared emissivity is 65~99%.
Citation Information
Patent Citations
Surface modification method for nanometer titanium dioxide
CN102660154A
Organic-inorganic material modified titanium dioxide (TiO2) nano composite combining sun protection factor strengthening agent and preparation method
CN102813609A
Metal oxide particles containing titanium oxide coated with silicon dioxide-tin(IV) oxide complex oxide?
CN103717535A
Preparation method of transparent radiation cooling material
CN115197477A
Method for preparing uvioresistant polyester by nanometer titania in situ
CN1552764A
Cited By
Anti-infrared lens and preparation method thereof
CN117075231A
Metastructure photonic crystal core-shell filler and preparation method and application thereof, radiation refrigeration film and preparation method and application thereof
CN120742458A
A hyperstructured photonic crystal core-shell filler, a preparation method and application thereof, and a radiation cooling film, a preparation method and application thereof
CN120742458B
